The type of contact mat affects vertical jump height estimated from flight time - J. García-López; J. A. Rodriguez-Marroyo; R. Pernía; M. C. Ávila; J. G. Villa (Asociación Española de Ciencias del Deporte, 2010)
Measuring flight time (Ft) on a contact mat is a common methodology to estimate vertical jump height. The aims of this study were: a-to analyze the influence of the contact mat technology on Ft, and b-to verify the validity and reliability of a new optoelectronic contact mat. Eighty-nine physical students performed 3 maximal jumps which were simultaneously registered by one force plate (FP) and two contact mats: ErgoJump Plus (EJ) and SportJump System Pro (SJ). They which were performed in a randomized order in the directions longitudinal and transversal with respect to PF. EJ underestimated Ft in 50.8 ms, while SJ underestimated it in 10.6 ms. Jump height did not affect these differences, although they increased when the jump direction was transversal in EJ. Correlation PF-EJ (r=0.6597) was lower than PF-SJ one (r=0.9992). Coefficient of variation of EJ (6.61±4.81%*) was higher than SJ (1.21±0.81%) and PF (1.19±0.78%) ones. The contact mat technology (optoelectronics vs. mechanics) had a great influence on both Ft and vertical jump height; therefore these instruments should be validated before using them in scientific studies. The new system SJ that use laser technology, was valid and reliable to measure vertical jumps. Key Words: biomechanics, instrumentation, vertical jump, contact mat.